Kyphoplasty is not Superior to Vertebroplasty in Restoring Vertebral Height in the Long Term - Alim Can Baymurat; Ferid Abdulaliyev; Asim Ahmadov; Muhammed Furkan Tosun; Mustafa Melik Can; Cem İsmail Güngör; Alpaslan Şenköylü (Gazi Medical Journal)
Objective: The aim of this study was to evaluate whether kyphoplasty (KP) is superior to vertebroplasty (VP) in restoring spinal height in the long term. Methods: The study encompassed a cohort of 33 patients aged between 42 and 90 years, with a follow-up period of at least 5 years, who had undergone either KP (n=16) or VP (n=17) for the diagnosis of osteoporotic vertebral fractures at our institution. Clinical comparisons were conducted on the basis of Oswestry scores, EuroQol-5 Dimension (EQ-5D), and visual analog scale (VAS) scores, while radiological assessments were performed considering fractured vertebral height and local kyphosis angle values. Evaluations were conducted across preoperative, postoperative, and last control radiographs. Results: In both cohorts, the mean age was comparable, and there was no significant difference in the follow-up duration (p=0.126). Regarding radiological assessments during the early postoperative phase, KP patients exhibited a noteworthy enhancement in the anterior vertebral column height (mean, from 1.3471 mm to 2.0941 mm), middle vertebral column height (mean, from 1.3375 mm to 1.6437 mm), and local kyphosis angle improvement (mean, from 17.88° to 7.81°). However, the last control values demonstrated similar outcomes in both groups (KP patients: 1.4412 mm, 1.4063 mm, 13.69°; VP patients: 1.2813 mm, 1.3176 mm, 17.18°). In addition, there were no statistically significant differences in Oswestry scores, EQ-5D index, and VAS scores between the two groups. Conclusion: According to our study, KP appears to be an effective method in the early treatment of painful collapsed vertebral fractures, but it was not observed to be superior to VP in the long term.